Oleosomes in almonds and hazelnuts: structural investigations by NMR - Trapp, Lena; Schacht, Hilke; Nirschl, Hermann; Guthausen, Gisela (Frontiers in Physics, 2025)
Oleosomes are lipid-containing organelles that store oils and fats in the tissues of seeds such as almonds and hazelnuts. A comprehensive and detailed understanding and measurement of their size and distribution is necessary to capture the physical properties of almond- or hazelnut-containing foods and to improve their quality. During processing, almonds and hazelnuts are blanched or roasted and crushed, leading to structural changes in their tissues. In addition, nut butter contains quasi-free oil. Pulsed-field gradient nuclear magnetic resonance (PFG-NMR) is applied to determine the size distribution of the oleosomes and to monitor the structural changes along the process chain. A model established for droplet size determination in emulsions was applied and extended to the present case.